Understanding lung sounds - Lehrer, Steven (Philadelphia : W. B. Saunders, 2002)
Understanding Lung Sound, third edition guides you through the sounds and skills of lung auscultation
System requirements : Windows PC ; Microsoft Windows 95 or higher, Pentium 166 equivalent or higher, 8 MB of RAM, CD-ROM drive, Windows CD Player, Media Player, Real Jukebox, or related media player, Sound card, Speakers
System requirements : Macintosh ; Mac Power PC or higher, 120-MHz processor or higher, 8 MB of RAM, CD-ROM drive, Sound card, Speakers
Keywords: Respiratory Sounds -- diagnosis; Auscultation